Calcium Isotope Ratios (δ44/40Ca) of Thirty‐Four Geological Chinese Reference Materials Measured by Thermal Ionisation Mass Spectrometry. Issue 2 (27th February 2022) - Liu, Fang; Li, Xin; Zhang, Zhaofeng; Bai, Jianghao; An, Yajun
Abstract : High‐precision calcium isotopic ratios of thirty‐four Chinese geological reference materials, including igneous, metamorphic and sedimentary rocks, river/marine sediments and soils, are reported. Measurements were conducted by thermal ionisation mass spectrometry (Triton TIMS) using a 42 Ca– 43 Ca double spike. These reference materials cover a wide range of chemical compositions with CaO ranging from 0.10 to 51.1% m / m . The δ 44/40 Ca variation of igneous rocks was up to 0.75‰, ranging from 0.61 ± 0.06‰ to 1.35 ± 0.04‰. Two metamorphic rocks yielded δ 44/40 Ca of 0.39 ± 0.02‰ and 0.86 ± 0.02‰, respectively. δ 44/40 Ca values of sedimentary rocks varied from −0.14 ± 0.09‰ to 0.98 ± 0.12‰, suggesting significant isotopic fractionation during low‐temperature processes. Like sedimentary rocks, river/marine sediments and soil displayed large Ca isotopic variations, with δ 44/40 Ca spanning from 0.12 ± 0.06‰ to 0.77 ± 0.03‰ and −0.09 ± 0.11‰ to 0.74 ± 0.08‰, respectively. The comprehensive data set reported in this study serves as a reference for quality assurance and inter‐laboratory comparison for high‐precision Ca isotopic studies. Abstract : Key Points δ 44/40 Ca values of thirty‐four Chinese geological reference materials are systematically reported. The observed large δ 44/40 Ca variation (up to 1.49‰) suggests significant Ca isotopic fractionation in nature. These comprehensive data can serve as a reference values for quality assurance and laboratory comparison purposes.